Conductor repair method

By using conductor repair materials of polymer substrates and metal powder fibers for low-temperature curing and repair, and covering the insulating isolation film, the problems of corrosion and reduced conductivity after conductor repair are solved, and efficient conductor repair is achieved, suitable for high-voltage cable systems Repair.

CN119207888AActive Publication Date: 2024-12-27STATE GRID BEIJING ELECTRIC POWER CO +2
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411310284.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

In the prior art, conductor repair methods require high temperature repair, and after repair, there are prone to conductor corrosion, reduced conductivity and reduced reliability problems. The corrosion potential of conventional repair materials and conductors is too large, resulting in serious contact corrosion and crevice corrosion.

Method used

The conductor repair material composed of polymer substrate, metal powder and metal fibers is used for low-temperature curing and repair, and the insulating repair material is covered on the repair interface to form a self-curing insulation film, reducing corrosion potential difference, improving conductivity and corrosion resistance.

Benefits of technology

It realizes conductor repair under low temperature conditions to maintain the original performance of the conductor. The repaired conductor has good conductivity, waterproofness and mechanical properties, avoids conductor corrosion, and is suitable for the repair of high-voltage cable systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119207888A_ABST
    Figure CN119207888A_ABST
Patent Text Reader

Abstract

The invention provides a conductor repairing method. The method comprises the following steps: filling a to-be-repaired part of a conductor with a conductor repair material, and then performing first curing to form a repair interface at the to-be-repaired part of the conductor; covering the surface of the repairing interface with an insulating repairing material, and then performing second curing to form an insulating isolating film on the surface of the repairing interface; the conductor repair material comprises a polymer base material, an additive, metal powder and metal fibers, the insulation repair material comprises a polymer base material and an additive. The metal powder and the metal fiber substances are added, good conductivity can be kept while the corrosion potential difference is greatly reduced, a self-curing insulating waterproof isolating membrane is formed by using an insulating repairing material, the self-curing insulating waterproof isolating membrane has good corrosion resistance and high mechanical strength, the repairing process can be carried out under the low-temperature condition, and the service life of the insulating repairing material is prolonged. The repaired conductor has good conductivity, corrosion resistance, waterproofness and mechanical property, and is suitable for repairing the cable terminal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal conductor repair, and in particular to a conductor repair method. Background Art

[0002] High-voltage cables and terminals are expensive, but conductor corrosion, cracks and other defects or failures often occur. Once this happens, the entire joint or the entire cable needs to be replaced, resulting in huge economic losses. Currently, there is no reliable technology report on repairing metal conductors at low temperatures and with corrosion resistance reliability. Conventional repair methods will aggravate the corrosion of metal conductors because there is a potential difference between the conductor and the repair material in the repair area.

[0003] In order to prevent other materials and structures inside the cable from being damaged by high temperature, high-temperature repair methods such as welding and melt casting cannot be used. Conventional repair materials are conductive carbon-based materials, and there are contact corrosion and crevice corrosion phenomena between them and the gaps between them and metal conductors. This is a deterioration phenomenon caused by the difference in corrosion potential between metal materials and dissimilar materials. In the cable system, the conductor inevitably has current passing through it, which causes its current density to be much higher than that of ordinary metal components, thereby increasing the migration rate of electrons and ions, causing corrosion to intensify, resulting in serious consequences such as hydrogen evolution and conductor damage. The repair material needs to meet the requirements of high conductivity while also having a certain degree of mechanical properties, bonding properties, etc.

[0004] At present, when using conductor repair materials on the market such as aluminum fillers (the matrix is ​​mainly epoxy resin) for repair, the following problems will occur: these materials have poor conductivity, low adhesion to conductors, inconvenient use, and the corrosion potential between them and the conductor is too different (most of the conductive additives inside are carbon-based materials such as carbon black powder, graphene, and untreated carbon nanotubes). After repair, it is easy to cause contact corrosion and crevice corrosion of the conductor, and cannot effectively repair conductor damage in fields such as high-voltage cable transmission lines. Summary of the invention

[0005] The main purpose of the present invention is to provide a conductor repair method to solve the problems in the prior art that the conductor repair method requires high temperature repair, is difficult to implement, and is prone to conductor corrosion, reduced conductivity, and reduced reliability after repair.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a conductor repair method is provided, comprising the following steps: step S1, filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing to form a repair interface at the part to be repaired of the conductor; step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing to form an insulating isolation film on the surface of the repair interface; wherein the conductor repair material comprises a polymer matrix, an additive, a metal powder and a metal fiber; and the insulating repair material comprises a polymer matrix and an additive.

[0007] Furthermore, the conductor repair material includes 100 parts of a polymer matrix, 1 to 2 parts of an additive, 20 to 50 parts of a metal powder and 20 to 38 parts of a metal fiber; the insulation repair material includes 100 parts of a polymer matrix and 1 to 2 parts of an additive.

[0008] Further, the polymer matrix includes condensation silicone rubber and / or EVA; preferably, the condensation silicone rubber includes one or more of dealcoholized silicone rubber, deoxime silicone rubber and deacetone silicone rubber; and / or the VA content in the EVA is 18-40%.

[0009] Furthermore, the additive includes maleic anhydride and / or zeolite powder; preferably, the size of the zeolite powder is 100-8000 mesh.

[0010] Furthermore, the size of the metal powder is 100-8000 mesh; preferably, the metal powder includes one or more of aluminum powder, copper powder, lead powder, nickel powder, silver powder, gold powder and platinum powder; more preferably, the metal powder includes aluminum powder and / or copper powder.

[0011] Furthermore, the metal fiber has a diameter of 10 to 30 μm and an aspect ratio of 10 to 30; preferably, the metal fiber includes one or more of aluminum fiber, copper fiber, lead fiber, nickel fiber, silver fiber, gold fiber and platinum fiber; more preferably, the metal fiber includes aluminum fiber and / or copper fiber.

[0012] Furthermore, the first curing temperature is 0 to 50° C., and the time is 0.25 to 24 hours.

[0013] Furthermore, the temperature of the second curing is 0 to 50° C., and the time is 0.25 to 24 hours, preferably 10 to 15 hours.

[0014] Furthermore, the thickness of the insulating isolation film is 0.01-50 mm.

[0015] Furthermore, step S1 also includes the following steps: physically polishing and chemically cleaning the part of the conductor to be repaired in sequence, and then filling the conductor repair material into the part of the conductor to be repaired; preferably, using one or more of alcohol, water and toluene for chemical cleaning.

[0016] By applying the technical solution of the present invention, a polymer substrate having good adhesion to the metal conductor is used for repair, and metal powder and metal fiber materials having a corrosion potential close to that of the conductor material are added, the corrosion potential difference can be greatly reduced while maintaining good conductivity. After the conductor repair material has basically repaired the conductor defect, an insulating repair material having the same base material as the conductor repair material is used to cover the formed repair interface surface to form a self-curing insulating waterproof isolation film, which has good adhesion and therefore does not require the addition of adhesives, and also has good anti-corrosion performance and high mechanical strength.

[0017] The present invention provides a conductor repair method that is not prone to conductor corrosion and has high conductivity and reliability after repair. The repair process can be carried out under low temperature conditions or under power, maintaining the original performance of the metal conductor. The repaired conductor has good conductivity, waterproofness and mechanical properties, and meets the use requirements in various harsh environments. The low-temperature repair method for metal conductors of the present invention has the advantages of simple operation, significant effect, and a wide range of applications. It is suitable for repairing cable terminals, provides a new solution for cable system maintenance and service life extension, and has broad application prospects in the field of repairing high-voltage system conductors. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 A schematic diagram of a repair process according to an embodiment of the present invention is shown;

[0020] Figure 2 The SEM morphology of the repaired surface of the repaired cable conductor after immersion in water according to Comparative Example 1 is shown;

[0021] Figure 3 The SEM morphology of the repaired surface of the repaired cable conductor after immersion in water according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0023] As described in the background of the present invention, the existing conductor repair method requires high temperature repair, is not easy to implement, and is prone to conductor corrosion, reduced conductivity, and reduced reliability after repair. In order to solve the above problems, in a typical embodiment of the present invention, a conductor repair method is provided, comprising the following steps: step S1, filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing to form a repair interface at the part to be repaired of the conductor; step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing to form an insulating isolation film on the surface of the repair interface; wherein the conductor repair material includes a polymer matrix, an additive, a metal powder and a metal fiber; the insulating repair material includes a polymer matrix and an additive.

[0024] Specifically, the conductor repair material is first filled into the repair shape template (optionally) to the defects, cracks, gaps waiting to be repaired of the conductor, and then the first curing is carried out. After the initial solidification, a repair interface is formed at the part of the conductor to be repaired; then the insulating repair material is covered on the surface of the repair interface, and the interface between the conductor repair material and the conductor is covered, and then a second curing is carried out to make the conductor repair material and the insulating repair material completely cured to form a self-curing insulating waterproof isolation film on the surface of the repair interface to isolate the electrolyte and prevent the presence of electrolyte at the contact point of the two conductive materials, so as to eliminate contact corrosion and fill the gap between the two conductive materials, thereby eliminating crevice corrosion, so that the repaired conductor has good conductivity, corrosion resistance and mechanical properties.

[0025] The metal powder and metal fiber have similar corrosion potentials to the conventional conductor to be repaired. The conductor repair material of the present invention uses metal powder and metal fiber as conductive fillers, uses metal fibers with similar corrosion potentials to the conductor material to be repaired to construct a conductive network, and adds metal powder with similar corrosion potentials to the conductor material to be repaired to synergistically improve conductivity. Using materials with a corrosion potential close to that of the conductor for repair can also help reduce the electrochemical reactions that may occur after repair and improve the stability of the repair effect.

[0026] The insulating repair material of the present invention is mainly used to isolate the conductor interface after the initial repair from the conductor repair material interface. Because its resistivity is much higher than that of the conductor, the current will not flow through this layer, and it can also effectively isolate the electrolyte and will not cause contact corrosion. In addition, the insulating repair material has the same non-metallic components as the conductor repair material and has self-curing ability, so there is no need to introduce additional adhesives that will cause metal surface corrosion, which improves the moisture resistance of the repaired part, improves the corrosion resistance while having adhesion, and prolongs the service life of the conductor.

[0027] A schematic diagram of the repair process of an embodiment of the present invention is shown in FIG. Figure 1As shown, a small potential difference between the conductor repair material and the metal material to be repaired is an important advantage because it can reduce or prevent the occurrence of electrochemical corrosion. In the case of contact between the two materials, if the potential difference is small, then the metal material is less likely to be affected by electrochemical corrosion. This is because a smaller potential difference means that less current is generated during the electrochemical corrosion process, thereby reducing the dissolution and corrosion of the metal material.

[0028] In addition, using an insulating isolation film with the same matrix as the conductor repair material (which can increase the adhesion to the conductor repair material) to cover the interface between the conductor repair material and the metal material also helps prevent the electrolyte from entering the contact interface, further reducing the risk of electrochemical corrosion. The insulating isolation film can prevent the penetration of electrolytes, thereby reducing the possibility of current passing. Due to the high resistance, when contacting the metal surface, the current will bypass the insulating isolation film and flow from other locations. Therefore, the insulating isolation film protects the interface between the fragile conductor repair material and the material to be repaired, preventing the intrusion of moisture or other electrolytes, and reducing the risk of electrochemical corrosion.

[0029] In summary, the small potential difference between the conductor repair material and the metal material to be repaired, the isolation by the insulating isolation film, and the large resistance all help reduce the risk of electrochemical corrosion and protect the metal material from corrosion.

[0030] The present invention provides a conductor repair method that is not prone to conductor corrosion and has high conductivity and reliability after repair. The repair process can be carried out under low temperature conditions or under power, maintaining the original performance of the metal conductor. The repaired conductor has good conductivity, waterproofness and mechanical properties, and meets the use requirements in various harsh environments. The low-temperature repair method for metal conductors of the present invention has the advantages of simple operation, significant effect, and a wide range of applications. It is suitable for repairing cable terminals, provides a new solution for cable system maintenance and service life extension, and has broad application prospects in the field of repairing high-voltage system conductors.

[0031] In a preferred embodiment, the conductor repair material includes 100 parts of polymer matrix, 1-2 parts of additives, 20-50 parts of metal powder and 20-38 parts of metal fiber by weight; the insulation repair material includes 100 parts of polymer matrix and 1-2 parts of additives. The conductor repair material composed of the above composition is more conducive to improving the conductivity by synergistically constructing a conductive network with metal fiber and metal powder, and is also conducive to synergistically improving the corrosion resistance by synergistically improving the polymer matrix and additives, and the reliability of the repair method is further improved.

[0032] In order to further improve the adhesion between the material used for conductor repair and the metal conductor and extend the service life of the conductor after repair, in a preferred embodiment, the polymer substrate includes condensation silicone rubber and / or EVA; preferably, the condensation silicone rubber includes one or more of dealcoholized silicone rubber, deoxime silicone rubber and deacetone silicone rubber; and / or the VA content in the EVA is 18-40%.

[0033] In a preferred embodiment, the additive includes maleic anhydride and / or zeolite powder; preferably, the size of the zeolite powder is 100-8000 mesh. The above additive can better absorb the small molecular substances released by the curing of the polymer substrate, further avoid corrosion of the metal, and ensure a smooth surface.

[0034] In the specific implementation process, the conductive network construction filler with a corrosion potential similar to that of the conductor to be repaired can be flexibly determined according to the repair scenario. In a preferred embodiment, the size of the metal powder is 100 to 8000 mesh; preferably, the metal powder includes one or more of aluminum powder, copper powder, lead powder, nickel powder, silver powder, gold powder and platinum powder; more preferably, the metal powder includes aluminum powder and / or copper powder. The above-mentioned ultrafine spherical metal powder is conducive to further improving the conductivity of the conductive material by utilizing its metallic properties, thereby further increasing the conductivity of the repaired conductor.

[0035] Based on similar reasons, in the specific implementation process, the fiber filler with a corrosion potential similar to that of the conductor to be repaired can be flexibly determined according to the metal matrix to be repaired to construct a conductive network. In a preferred embodiment, the diameter of the metal fiber is 10 to 30 μm, and the aspect ratio is 10 to 30; preferably, the metal fiber includes one or more of aluminum fiber, copper fiber, lead fiber, nickel fiber, silver fiber, gold fiber and platinum fiber; more preferably, the metal fiber includes aluminum fiber and / or copper fiber.

[0036] In a preferred embodiment, the first curing temperature is 0-50° C. and the time is 0.25-24 hours, so that the conductor repair material can be initially cured to a more suitable degree, forming a repair interface that is more convenient for subsequent insulation repair material to cover.

[0037] In order to make the conductor repair material and the insulation repair material cure more fully during the repair process, in a preferred embodiment, the second curing temperature is 0 to 50° C. and the time is 0.25 to 24 hours, preferably 10 to 15 hours.

[0038] In a preferred embodiment, the thickness of the insulating isolation film is 0.01-50 mm. The insulating isolation film with the above thickness can further improve the corrosion resistance and reliability of the repaired conductor.

[0039] In order to make the part of the conductor to be repaired smooth and flat before repair, without residual corrosion products, so as to be more conducive to the attachment and retention of the repair material, in a preferred embodiment, step S1 also includes the following steps: the part of the conductor to be repaired is physically polished and chemically cleaned in sequence, and then the conductor repair material is filled into the part of the conductor to be repaired; preferably, one or more of alcohol, water and toluene are used for chemical cleaning. Preferably, one or more of a knife, a cutter, a grinder, scissors, and pliers are used to clean the conductor fracture (the part to be repaired), remove the corrosion products on the cross section (if any), and grind the fracture with one or more of a grinder and sandpaper.

[0040] Typically, but not limiting, the conductor repair material comprises 100 parts of a polymer matrix, 1 part, 1.5 parts, 2 parts or any range of two values ​​of an additive, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or any range of two values ​​of a metal powder, and 20 parts, 25 parts, 30 parts, 35 parts, 38 parts or any range of two values ​​of a metal fiber; the insulation repair material comprises 100 parts of a polymer matrix, 1 part, 1.5 parts, 2 parts or any range of two values ​​of an additive.

[0041] Typically but not limiting, the size of the metal powder is 100 mesh, 1000 mesh, 2000 mesh, 3000 mesh, 4000 mesh, 5000 mesh, 6000 mesh, 7000 mesh, 8000 mesh or a range consisting of any two of them; the diameter of the metal fiber is 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or a range consisting of any two of them, and the aspect ratio is 10, 15, 20, 25, 30 or a range consisting of any two of them.

[0042] Typically but not limiting, the temperature of the first curing is 0°C, 10°C, 20°C, 30°C, 0°C, 50°C or a range consisting of any two of them, and the time is 0.25h, 1h, 2h, 5h, 10h, 15h, 20h, 24h or a range consisting of any two of them; the temperature of the second curing is 0°C, 10°C, 20°C, 30°C, 0°C, 50°C or a range consisting of any two of them, and the time is 0.25h, 1h, 2h, 5h, 10h, 15h, 20h, 24h or a range consisting of any two of them.

[0043] Typically but not limiting, the thickness of the insulating isolation film is 0.01 mm, 1 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm or a range consisting of any two of these values.

[0044] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0045] Unless otherwise specified, the conductor to be repaired in the embodiments and comparative examples is a cable, and the materials used can be conveniently purchased from the market or made by conventional methods in the art. Exemplary sources are as follows:

[0046] Ultrafine spherical aluminum powder: Henan Yuanyang Powder Technology Co., Ltd., FLPG 7.5;

[0047] Short diameter aluminum micron fiber: homemade, the aluminum wire was drawn using a wet continuous wire drawing machine at a drawing speed of about 1.0 m / min and a vacuum degree of 10×10 -5 Pa, stretched from 1.0 mm to 20 μm in outer diameter, and subsequently chopped with a fiber cutter to an aspect ratio of 20.

[0048] Example 1

[0049] The conductor repair material includes 100 parts of a polymer matrix (dealcoholized silicone rubber), 1.5 parts of an additive (maleic anhydride), 20 parts of ultrafine spherical aluminum powder and 35 parts of metal fiber (short-diameter aluminum micron fiber). The conductor repair material is obtained by mixing the above materials for 1 hour.

[0050] The insulation repair material includes 100 parts of a polymer base material (de-alcoholized silicone rubber) and 1.5 parts of an additive (maleic anhydride). The above materials are mixed for 1 hour to obtain the insulation repair material.

[0051] Step S1, cleaning and polishing the conductor fracture, cleaning the metal surface with anhydrous alcohol to make it smooth and flat; filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing at a temperature of 30° C. for 12 hours to form a repair interface at the part to be repaired of the conductor;

[0052] Step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing at a temperature of 30° C. for 12 hours to form an insulating isolation film on the surface of the repair interface with a thickness of 30 mm.

[0053] Example 2

[0054] The conductor repair material includes 100 parts of a polymer matrix (EVA, VA content is 30%), 1.5 parts of an additive (maleic anhydride), 20 parts of ultrafine spherical aluminum powder and 35 parts of metal fiber (short-diameter aluminum micron fiber). The conductor repair material is obtained by mixing the above materials for 1 hour.

[0055] The insulation repair material includes 100 parts of a polymer base material (de-alcoholized silicone rubber) and 1.5 parts of an additive (maleic anhydride). The above materials are mixed for 1 hour to obtain the insulation repair material.

[0056] Step S1, cleaning and polishing the conductor fracture, cleaning the metal surface with anhydrous alcohol to make it smooth and flat; filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing at a temperature of 30° C. for 12 hours to form a repair interface at the part to be repaired of the conductor;

[0057] Step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing at a temperature of 30° C. for 12 hours to form an insulating isolation film on the surface of the repair interface with a thickness of 30 mm.

[0058] Example 3

[0059] The difference from Example 1 is:

[0060] The conductor repair material includes 100 parts of a polymer matrix (EVA, VA content is 18%), 1 part of an additive (zeolite powder 100 mesh), 20 parts of a metal powder (aluminum powder, 100 mesh) and 38 parts of a metal fiber (aluminum fiber, diameter is 10 μm, aspect ratio is 10);

[0061] The insulation repair material includes 100 parts of a polymer matrix (EVA, VA content of 18%) and 1 part of an additive (zeolite powder 100 meshes).

[0062] Example 4

[0063] The difference from Example 1 is:

[0064] The conductor repair material includes 100 parts of a polymer matrix (EVA, VA content is 40%), 2 parts of an additive (zeolite powder 8000 mesh), 50 parts of a metal powder (copper powder, 8000 mesh) and 20 parts of a metal fiber (copper fiber, diameter is 30 μm, aspect ratio is 30);

[0065] The insulation repair material includes 100 parts of a polymer matrix (EVA, VA content of 40%) and 2 parts of an additive (zeolite powder 8000 mesh).

[0066] Example 5

[0067] The difference from Example 1 is:

[0068] Step S1, cleaning and polishing the conductor fracture, cleaning the metal surface with anhydrous alcohol to make it smooth and flat; filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing at a temperature of 0° C. for 24 hours to form a repair interface at the part to be repaired of the conductor;

[0069] Step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing at a temperature of 0° C. for 24 hours to form an insulating isolation film on the surface of the repair interface with a thickness of 50 mm.

[0070] Example 6

[0071] The difference from Example 1 is:

[0072] Step S1, cleaning and polishing the conductor fracture, cleaning the metal surface with anhydrous alcohol to make it smooth and flat; filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing at a temperature of 50° C. for a time of 0.25 h to form a repair interface at the part to be repaired of the conductor;

[0073] Step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing at a temperature of 50° C. for 0.25 h to form an insulating isolation film on the surface of the repair interface with a thickness of 0.01 mm.

[0074] Comparative Example 1

[0075] The difference from Example 1 is that an aluminum repair agent (Hui Rui HR-8113 aluminum repair agent) is used to repair the conductor.

[0076] Comparative Example 2

[0077] The difference from Example 1 is that step S2 is not performed.

[0078] Performance Test:

[0079] The conductor repair materials and repaired conductors of the above-mentioned embodiments and comparative examples were subjected to performance tests, and the results are shown in Tables 1 and 2.

[0080] Peel strength test: According to GB / T 2791-1995, the prepared conductor repair material was placed in a flat vulcanizer at 120°C to prepare a 1cm×10cm×0.2cm sample, and then the sample and 1cm×10cm×0.1cm aluminum sheet were press-formed in a flat vulcanizer (EVA base was hot-pressed at 120°C and 15Mpa for 15 minutes, and silicone rubber base was hot-pressed at room temperature and 15Mpa for 15 minutes) to obtain a hot-pressed conductor repair material / aluminum sheet composite material sample. The conductor repair material / aluminum sheet composite material sample was stretched using a tensile testing machine, and the tensile force obtained was used as the peel strength.

[0081] Conductivity test:The conductor repair material was pressed into a 10mm×10mm×3mm sheet. The polarization-depolarization curve was tested using three electrodes (the bottom electrode was connected to low voltage, the middle electrode was connected to high voltage, and the outer electrode at the high voltage end was grounded). The conductive properties of the conductor were obtained by fitting.

[0082] Corrosion Potential Test: The conductor repair material was made into a 1cm×1cm×0.2mm thin sheet as an auxiliary electrode, clamped with a platinum electrode clamp and immersed in an electrolytic cell filled with 3.5% sodium chloride together with a 1cm×1cm×0.2mm aluminum working electrode and a saturated calomel reference electrode. The open circuit potential was tested using a Chenhua electrochemical workstation CHI760, and the time was set to 400s.

[0083] Neutral salt spray corrosion test: After the repaired conductor material has been cured for 24 hours, its corrosion performance in a salt spray environment is evaluated according to the standard GB / T12967.3-2022. The test sample is exposed to a salt spray environment with sodium chloride (concentration of 50g / L) for 48 hours, and a salt water solution is sprayed on the sample surface. The degree of corrosion of the sample will be monitored and evaluated by visually observing the corrosion marks on the sample surface and calculating the corrosion area.

[0084] Current soaking corrosion test: After the repaired conductor material has been cured for 24 hours, the repaired position is immersed in water and a 0.01 mA current is applied for 48 hours to observe the corrosion degree of the connection. After the test is completed, SEM morphology characterization is performed (when testing SEM, the insulating isolation film covering the interface is uncovered to characterize the interface).

[0085] Table 1

[0086]

[0087] It can be seen from Table 1 that compared with Comparative Example 1, the conductor repair material of Comparative Example 2 has higher peeling strength, lower resistivity, and very low potential difference in corrosion potential, showing more superior performance; compared with Comparative Example 2, the conductor repair materials of each embodiment have good insulation properties.

[0088] Table 2

[0089]

[0090] As can be seen from the above, the appearance of Comparative Examples 1 and 2 shows that there are corrosion products on the surface, the protection level is not passed (level 8), and the discoloration is serious. For the samples of each embodiment, there is no sign of corrosion on the surface, the protection level is passed (level 9.5), and the discoloration is less or not. From the results of the current soaking corrosion test, it can be seen that the sample of Comparative Example 1 has serious corrosion at the connection, while the sample of Example 1 has almost no corrosion at the connection.

[0091] The SEM morphology of the repaired surface of the repaired cable conductor of Comparative Example 1 after immersion in water is shown in Figure 2 ; The SEM morphology of the repaired surface of the cable conductor after immersion in water in Example 1 is shown in Figure 3 It can be seen from the SEM image that in the current-immersion corrosion test, the corrosion degree at the interface between the conductor to be repaired and the conductor repair material in Example 1 is relatively small, showing better corrosion resistance and insulation performance, and is suitable for repair work.

[0092] As can be seen from the above, compared with the comparative example, each embodiment of the present invention uses a polymer substrate with good adhesion to the metal conductor for repair, and adds metal powder and metal fiber materials with a corrosion potential close to that of the conductor material, which can significantly reduce the corrosion potential difference while maintaining good conductivity. After the conductor repair material has basically repaired the conductor defect, an insulating repair material with the same base material as the conductor repair material is used to cover the surface of the formed repair area to form a self-curing insulating waterproof isolation film, which has good adhesion and therefore does not require the addition of adhesives, and also has good anti-corrosion properties and high mechanical strength. The method of the present invention of first using a conductor repair material to repair the conductor and then covering the repair interface with an insulating repair material can overcome the problem of easy corrosion of the conductor after repair.

[0093] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A conductor repair method, characterized in that: The following steps are involved: Step S1, filling the conductor repair material into the part to be repaired of the conductor, and then performing a first curing to form a repair interface at the part to be repaired of the conductor; Step S2, covering the surface of the repair interface with an insulating repair material, and then performing a second curing to form an insulating isolation film on the surface of the repair interface; Wherein, the conductor repair material comprises a polymer matrix, an additive, metal powder and metal fiber; and the insulation repair material comprises the polymer matrix and the additive.

2. The conductor repair method according to claim 1, characterized in that: By weight, The conductor repair material comprises 100 parts of the polymer matrix, 1 to 2 parts of the additive, 20 to 50 parts of the metal powder and 20 to 38 parts of the metal fiber; The insulation repair material comprises 100 parts of the polymer base material and 1 to 2 parts of the additive.

3. The conductor repair method according to claim 1 or 2, characterized in that: The polymer substrate includes condensation silicone rubber and / or EVA; preferably, the condensation silicone rubber includes one or more of dealcoholized silicone rubber, deoxime silicone rubber and deacetone silicone rubber; and / or the VA content in the EVA is 18-40%.

4. The conductor repair method according to any one of claims 1 to 3, characterized in that: The additives include maleic anhydride and / or zeolite powder; preferably, the size of the zeolite powder is 100-8000 mesh.

5. The conductor repair method according to any one of claims 1 to 4, characterized in that: The size of the metal powder is 100-8000 mesh; preferably, the metal powder includes one or more of aluminum powder, copper powder, lead powder, nickel powder, silver powder, gold powder and platinum powder; more preferably, the metal powder includes aluminum powder and / or copper powder.

6. The conductor repair method according to any one of claims 1 to 5, characterized in that: The metal fiber has a diameter of 10 to 30 μm and an aspect ratio of 10 to 30; preferably, the metal fiber includes one or more of aluminum fiber, copper fiber, lead fiber, nickel fiber, silver fiber, gold fiber and platinum fiber; more preferably, the metal fiber includes aluminum fiber and / or copper fiber.

7. The conductor repair method according to any one of claims 1 to 6, characterized in that: The temperature of the first curing is 0-50° C., and the time is 0.25-24 hours.

8. The conductor repair method according to any one of claims 1 to 7, characterized in that: The temperature of the second curing is 0 to 50° C., and the time is 0.25 to 24 hours, preferably 10 to 15 hours.

9. The conductor repair method according to any one of claims 1 to 8, characterized in that: The thickness of the insulating isolation film is 0.01-50 mm.

10. The conductor repairing method according to any one of claims 1 to 9, characterized in that: The step S1 further includes the following steps: physically grinding and chemically cleaning the part of the conductor to be repaired in sequence, and then filling the conductor repair material into the part of the conductor to be repaired; preferably, one or more of alcohol, water and toluene are used for the chemical cleaning.

Citation Information

Patent Citations

  • Conductive carbon fiber repairing tape and method thereof

    CN107858131A

  • Middle-high voltage cross-linked polyethylene insulation fault repair power cable and repair method

    CN115065009A

  • Pretreatment method and smearing device for improving surface defects of cable conductor

    CN118629711A

  • Cable joint

    GB9815704D0

  • Method for repairing disconnection of flat cable

    JP2010273437A